Writing Therapy in Children with Neurodevelopmental Disorder (ADHD & Autism) by Parents: Module Validation - Lisa Nur Farida; Ira Paramastri (Faculty of Psychology, Universitas Gadjah Mada, 2023)
Therapy modules that are systematically arranged, structured and easy to use become very meaningful when the learning system must be carried out independently. The aim of the study is to examine the validity of the writing therapy module “TM3”. This module is designed so that parents can use it to train and improve the attention-focusing abilities of children with ADHD & Autism through writing therapy. Participants involved in this study consisted of 5 clinical psychologists, 5 occupational therapists and 42 parents of children diagnosed with ADHD and Autism, all of which were recruited through a semi-online survey. Validation includes two processes, namely: content validation and empirical validation. The results of the validation of the content of the module are 0.827 and the readability validation is 0.833 (v> 0.5) with a good validity category. In testing the empirical validity based on responses from 42 participants, the reliability value (r11) = 0.787 was included in the high category. This shows that the “TM3” writing therapy module is valid both empirically and content, and the module can be used to train (therapy) children.